2020
DOI: 10.1038/s42003-020-01320-6
|View full text |Cite
|
Sign up to set email alerts
|

Reward uncertainty asymmetrically affects information transmission within the monkey fronto-parietal network

Abstract: A central hypothesis in research on executive function is that controlled information processing is costly and is allocated according to the behavioral benefits it brings. However, while computational theories predict that the benefits of new information depend on prior uncertainty, the cellular effects of uncertainty on the executive network are incompletely understood. Using simultaneous recordings in monkeys, we describe several mechanisms by which the fronto-parietal network reacts to uncertainty. We show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
4
8
0
Order By: Relevance
“…Studies have also suggested that beta-band oscillations behave as propagating TWs in sensory, motor and premotor structures (e.g., in humans ((Stolk et al, 2019; Takahashi et al, 2011), monkeys (Rubino et al, 2006; Takahashi et al, 2015), and cats (Roelfsema et al, 1997))). Our results extend the evidence for this claim to reward processing, and suggest that at least some of the previously reported effects of reward on the LFP oscillations in the frontal lobe (Taghizadeh et al, 2020) may in fact reflect signals that propagate in specific directions as planar traveling waves (Hamid et al, 2021).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Studies have also suggested that beta-band oscillations behave as propagating TWs in sensory, motor and premotor structures (e.g., in humans ((Stolk et al, 2019; Takahashi et al, 2011), monkeys (Rubino et al, 2006; Takahashi et al, 2015), and cats (Roelfsema et al, 1997))). Our results extend the evidence for this claim to reward processing, and suggest that at least some of the previously reported effects of reward on the LFP oscillations in the frontal lobe (Taghizadeh et al, 2020) may in fact reflect signals that propagate in specific directions as planar traveling waves (Hamid et al, 2021).…”
Section: Discussionsupporting
confidence: 86%
“…Our finding that TWs are sensitive to rewards is consistent with the reward-selective spiking activity shown by many frontal and parietal cells (Foley et al, 2020; Kennerley et al, 2009; Taghizadeh et al, 2020; Wallis and Kennerley, 2010), and with the fact that these cells have sustained activity with relatively long time-constants and encode cross-trial memories, including about statistically irrelevant prior rewards (Abrahamyan et al, 2016; Akrami et al, 2018; Foley et al, 2020; Genovesio et al, 2014; Lee et al, 2012; Mansouri et al, 2006; Scott et al, 2017). However, our results suggest that TWs reflect unique aspects of reward computations that differ from those encoded in individual cells.…”
Section: Discussionsupporting
confidence: 85%
“…Taking advantage of these behavioral observations, the field is beginning to learn how the brain controls our desire to know what rewards our future holds (Bromberg-Martin and Monosov, 2020;Gottlieb et al, 2020;Monosov, 2020;Taghizadeh et al, 2020). For example, we found that the anterior cingulate cortex (ACC) contains a population of cells that predict reward-uncertaintydriven information-seeking behavior, and that ACC projection targets in the basal ganglia (BG) causally contribute to the motivation to make information-seeking eye movements (Bromberg-Martin and Monosov, 2020;Monosov, 2020;White et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, direct investigation of projection neurons is still necessary to ascertain the route of the analytically inferred information transmission. Furthermore, examining task-dependent or learning-related changes in projection neurons can reveal the mechanisms underlying dynamic connectivity in this network (Pesaran et al, 2008;Suriya-Arunroj and Gail, 2019;Taghizadeh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%